Peningkatan Kreativitas Guru Pendidikan Agama Kristen Melalui Pengembangan Materi Pembelajaran Digital - Sadariani Zebua; Mortan Sibarani (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
Increasing the creativity of Christian religious education teachers through the development of digital learning materials is urgently needed because without developing digital learning materials, PAK teachers will experience a lag in digital information. This study aims to investigate the development of digital learning materials that can increase the creativity of Christian religious education teachers. In the digital era that continues to grow, the use of technology in Christian religious education has great potential to create a more interesting and effective learning experience. This study uses a type of qualitative research and involves literature studies to gain an in-depth understanding of the integration of Christian religious values in digital learning. The results of the study show that the development of digital learning materials can provide significant benefits in increasing the creativity of Christian religious education teachers. By integrating Christian religious values, teachers can create more innovative and creative teaching methods. The use of technological resources such as multimedia, video, and interactive software allows teachers to extend learning materials and create more engaging learning experiences for students.